2000
DOI: 10.1074/jbc.275.10.7021
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting G Protein-coupled Receptor Signaling Pathways with Membrane-permeable Blocking Peptides

Abstract: To determine the intracellular signaling mechanism of the 5-HT 2C receptor endogenously expressed in choroid plexus epithelial cells, we implemented a strategy of targeted disruption of protein-protein interactions. This strategy entails the delivery of conjugated membrane-permeable peptides that disrupt domain interaction at specific steps in the signaling cascade. As proof of concept, two peptides targeted against receptor-G protein interaction domains were examined. Only G q CT, which targets the receptor-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 54 publications
4
70
0
Order By: Relevance
“…The Gβγ i subunit is known to inhibit Ca 2+ entry via N-type Ca 2+ -channels [22;29]. Thus, we hypothesized that signaling via the Gβγ i subunit could represent a common mechanism of action in the attenuation of NE exocytosis by H 3 R and EP 3 R. Indeed, we found that the membrane-permeable Gβγ-blocking peptide [23], which prevented the imetit-induced MAPK activation in SH-SY5Y-H 3 cells, significantly attenuated the inhibition of K + -induced NE exocytosis elicited by imetit and sulprostone in cardiac sympathetic nerve endings. This suggests that neuronal Ca 2+ -channel blockade via the Gβγ isubunit plays a role in the H 3 R-and EP 3 R-mediated inhibition of NE exocytosis and that MAPK is an important upstream step in this pathway.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Gβγ i subunit is known to inhibit Ca 2+ entry via N-type Ca 2+ -channels [22;29]. Thus, we hypothesized that signaling via the Gβγ i subunit could represent a common mechanism of action in the attenuation of NE exocytosis by H 3 R and EP 3 R. Indeed, we found that the membrane-permeable Gβγ-blocking peptide [23], which prevented the imetit-induced MAPK activation in SH-SY5Y-H 3 cells, significantly attenuated the inhibition of K + -induced NE exocytosis elicited by imetit and sulprostone in cardiac sympathetic nerve endings. This suggests that neuronal Ca 2+ -channel blockade via the Gβγ isubunit plays a role in the H 3 R-and EP 3 R-mediated inhibition of NE exocytosis and that MAPK is an important upstream step in this pathway.…”
Section: Discussionmentioning
confidence: 93%
“…The Gβγ i subunit is known to inhibit Ca 2+ entry [22]; thus, the Gβγ i subunit could play a role in the H 3 R-mediated attenuation of NE exocytosis. To test this hypothesis we used a phosducin-like membrane-permeable Gβγ-blocking peptide [23]. As shown in Figure 8, the H 3 R agonist imetit (100 nM) and the EP 3 R agonist sulprostone (300 nM) each caused a ~60% attenuation of K + -induced NE exocytosis from guinea-pig heart synaptosomes.…”
Section: Mechanism(s) Of Pge 2 -Mediated Anti-exocytotic Effect Of H mentioning
confidence: 99%
“…Inositol triphosphate promotes intracellular calcium mobilization, while diacylglycerol stimulates the activity of protein kinase C (Exton, 1996). 5-Hydroxytryptamine 2A (5-HT) 2A receptors are a subtype of the 5-HT2 subfamily of receptors, known to stimulate the PLC pathway via Gα q (Chang et al, 2000). 5HT 2A receptors are widely distributed in brain, including cortex, caudate nucleus, olfactory tubercle, nucleus accumbens, and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Disrupting this protein-protein interaction, by introducing one of the binding domains into cell, can thus block specific pathways. Previous studies (34,37,38) have shown that the GPCR/G protein interaction can be disrupted in vitro by peptides derived from the C terminus of the G protein. This approach to analyze signaling has been limited, however, as most peptides do not readily penetrate the cell membrane.…”
Section: Microinjection Of Antibodies To the C Terminus Of G␣ Q/11 Ormentioning
confidence: 99%
“…We also generated peptides to inhibit G␣ s and G␤␥ signaling as controls. These inhibitory peptides are based on published sequences (34). The peptides were expressed as TAT fusion proteins to allow internalization.…”
Section: Fig 1 Effect Of Ptx On Gnrh-induced Erk Activation and C-fmentioning
confidence: 99%